Comparative Analysis of Prophetic Inheritance Systems and Legal Frameworks in Monotheistic Religions - Irwansyah, Shindu; Goffary, Irfan (Prodi Ilmu Hadis Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2023)
This study aims to provide a comprehensive comparative analysis of inheritance systems within the Abrahamic monotheistic religions: Islam, Christianity, and Judaism. Employing a qualitative approach and descriptive-analytical methodology, the research reveals key insights. Firstly, all three religions incorporate fundamental principles into their inheritance laws, reflecting ideals of equity, familial care, and religious commitment. Secondly, while variations exist in the execution of inheritance regulations, commonalities prevail, including recognition of inheritance rights for specific heirs such as children and spouses. Thirdly, significant differences emerge in the intricate details and implementation of inheritance rules. Islam features highly detailed and structured provisions, while Judaism allows more flexibility, and Christianity exhibits denominational variations. Lastly, religious authorities play a substantial role in resolving inheritance disputes across these religions. This study offers valuable insights for shaping fair and sustainable inheritance frameworks in diverse, multicultural societies